High level of quinolone resistance in Escherichia coli from healthy chicken broilers - Kmeť, Vladimír; Kmeťová, Marta (Folia microbiologica, 2010)
The development of resistance to quinolones (nalidixic acid, ciprofloxacin and enrofloxacin) in 2006-2008 was evaluated in 317 strains of Escherichia coli isolated from healthy chicken broilers from various farms. The isolates (2006/2007/2008) showed a high resistance to nalidixic acid (87/85/67 %), ciprofloxacin (CIP) (49/54/29 %) and enrofloxacin (ENR) (52/42/22 %). Nalidixic acid-resistant isolates with low level of MIC for CIP and ENR represented a single mutation; intermediary MIC for CIP and ENR were related to two mutations and high level resistance MIC for CIP (> or =4 mg/L) and ENR (> or =16 mg/L) represented three mutations (two in gyrA and one in parC). There was a correlation between the phenotype reading of high-level resistance and mutations in gyrA (Ser83Leu, Asp87Tyr or Asp87Asn) and parC (Ser80Ile) gene. Plasmid-mediated quinolone-resistance qnrS gene was detected in one Escherichia coli strain with a high level of ciprofloxacin resistance. Our results demonstrate the increase in occurrence of multiresistant E. coli strains with a high level of chromosomal and plasmid resistance to fluoroquinolones.
Keywords: financování organizované; kur domácí; Animals; chinolony; Quinolones; bakteriální chromozomy; mikrobiální testy citlivosti; Escherichia coli; Chickens; sekvence aminokyselin; substituce aminokyselin; Molecular Sequence Data; Anti-Bacterial Agents; DNA gyráza; Amino Acid Substitution; DNA Gyrase; Mutation, Missense; Amino Acid Sequence; proteiny z Escherichia coli; bakteriální léková rezistence; Financing, Organized; Microbial Sensitivity Tests; molekulární sekvence - údaje; missense mutace; plazmidy; DNA Topoisomerase IV; Plasmids; zvířata; antibakteriální látky; DNA-topoisomerasa IV; Drug Resistance, Bacterial; Escherichia coli Proteins; Chromosomes, Bacterial